Derechos humanos, sociedad civil, derecho privado: problemas de correlación - Evgen Kharytonov; Olena Kharytonova (Ius Humani. Jornal do direito, 2019)
The category of “human rights and freedoms”, the problems of protection and protection of such rights have repeatedly been the subject of research, but the question of their correlation with concepts such as “civil society”, “private law” has not been studied yet. This circumstance determines the expediency of a special study of this issue. Several methodological techniques have been used in the process of exploring issues related to this article. The main ones were civilization and conceptual methods. With the help of the “civilization” method, we explored “law” as a category inseparably related to civilization. The “concept” method helps to consider law in general, and private law as a concept (conceptus from the Latin: thought, representation, concept), that is, as a set of verbal expressions of a social phenomenon denoted by a particular term. In the conclusion, the authors state that there is a conflict in the field of human rights and the conflict of interests of members of civil society, the state resorts to a positive legal regulation of human behavior (taking into account the national mentality and influencing the formation and transformation of justice in the desired direction). The study reveals that there are no grounds for excessive concern about the “infinity” of human rights. This boundary is usually defined naturally, in the face of the rights and interests of other members of civil society.